2021
DOI: 10.3390/antibiotics10091091
|View full text |Cite
|
Sign up to set email alerts
|

The Internet: Friend or Foe of Antibiotic Resistance? Results of a Cross-Sectional Study among Italian University Students

Abstract: The study aims were to investigate knowledge and attitudes towards antibiotics and antibiotic resistance (ABR), and to assess the extent of practices regarding antibiotic consumption and Internet use among university students in Southern Italy. Data were collected through an anonymous online questionnaire from April 1 to April 14, 2021. The eligibility criteria for the study were: (i) age between 18 and 30 years and (ii) registered as an undergraduate student at the university. Among the 1051 sampled students,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…Given healthcare's rapid changes and speed at which technology is progressing, there is a need to support more regular updates of knowledge and maintain the health skills of individuals throughout life ( 45 ), using all potential resources (e.g., social media). In accordance with previous studies in the same area ( 46 , 47 ), social networks and government websites were reported as major sources of health information. Therefore, health organizations have to consider social media and the Internet within their communication strategy to promote the appropriate Web use for HIV-related information seeking, especially among young people who are the most digitally savvy population group ( 45 , 48 ).…”
Section: Discussionsupporting
confidence: 85%
“…Given healthcare's rapid changes and speed at which technology is progressing, there is a need to support more regular updates of knowledge and maintain the health skills of individuals throughout life ( 45 ), using all potential resources (e.g., social media). In accordance with previous studies in the same area ( 46 , 47 ), social networks and government websites were reported as major sources of health information. Therefore, health organizations have to consider social media and the Internet within their communication strategy to promote the appropriate Web use for HIV-related information seeking, especially among young people who are the most digitally savvy population group ( 45 , 48 ).…”
Section: Discussionsupporting
confidence: 85%
“…Misconceptions and lack of awareness about AMR that were identified in this study are common and align with the literature (e.g., McCullough et al, 2016;Bakhit et al, 2019;Bianco et al, 2021;Licata et al, 2021;Cantarero-Arevalo et al, 2022;McNulty et al, 2022;Hika et al, 2022). A common misconception that was identified in this study and consistent with previous literature is related to the in accurate belief that all infections (both viral and bacterial) can benefit from antibiotics use (Bianco et al, 2021;Licata et al, 2021;McNulty et al, 2022).…”
Section: Theme T2: Impressions Of the Changes In Antibiotic Dispensin...supporting
confidence: 85%
“…Isso seria benéfico para o público em geral, particularmente para os estudantes da área da saúde, pois, como estão em estágio de aprendizagem, seus conhecimentos e atitudes podem ser modificados, sendo esse um excelente motivo para abordar conceitos sobre o uso racional de medicamentos, em especial, os antibióticos. Com isso, é possível promover o conhecimento a respeito desse assunto para a população, o que poderá evitar a Research, Society and Development, v. 13, n. 1, e7813144698, 2024 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v13i1.44698 8 iminente pandemia por microrganismos patogênicos resistentes (Loni et al, 2023;Licata et al, 2021).…”
Section: Discussionunclassified